PENGARUH KEPEMILIKAN PEMERINTAH TERHADAP KINERJA KEUANGAN MELALUI DEWAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL INTERVENING - Nathania Hunardy; Josua Tarigan (Business Accounting Review, 2017)
This study aimed to prove that there was an influence between government ownership and financial performance through board independent as intervening variable in the manufacturing sector. The ownership structure in this study is measured using goverment ownership. Board independent measured by using the calculation of the proportion of board independent. This research uses two financial performance indicators Tobin's Q and Return on Assets. This study examined 445 firm year in the manufacturing sector listed in Indonesia Stock Exchange during 2011-2015. The results showed that government ownership tend to assist in improving the company's financial performance. This was indicated by goverment ownership that had significant positive effect on financial performance. The results also showed that goverment ownership had significant negative affect on the board independent. This means that the increasing government ownership structure in the company, the composition of board independent also tended to decrease. While, The independent board of commissioners had a significant negative influence on financial performance.